2012
DOI: 10.1161/circep.112.970863
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Repolarization and Sudden Cardiac Death During an Acute Coronary Event

Abstract: Background— Electrocardiographic early repolarization (ER) pattern has been previously associated with arrhythmic mortality and with an increased risk of ventricular fibrillation. We hypothesized that there is an association between ER and sudden cardiac death (SCD) during an acute coronary event. Methods and Results— The present study included 432 consecutive victims of SCD because of acute coronary event and 532 survivors of such an eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 24 publications
4
57
1
2
Order By: Relevance
“…The association of a initially existing J-wave pattern with future arrhythmic complications during acute STEMI was explained by the presence of heterogeneity of ventricular repolarization as a substrate predisposing to the development of ventricular arrhythmias in the setting of an acute ischemia trigger (22). In our study J-wave point elevation was observed in 0,2%, that is much lower than in the above mentioned studies -11-16% (18,19), and than the reported early repolarization (ER) prevalence in general population -4.5% (23). However, ER is known to be an age-dependant phenomenon, and in age group 60-70 years, corresponding the average age at the moment of historical ECG in our study, its prevalence appears to be in the range of 1.5% in women and 2-3% in man (23) thus being in line with our observations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The association of a initially existing J-wave pattern with future arrhythmic complications during acute STEMI was explained by the presence of heterogeneity of ventricular repolarization as a substrate predisposing to the development of ventricular arrhythmias in the setting of an acute ischemia trigger (22). In our study J-wave point elevation was observed in 0,2%, that is much lower than in the above mentioned studies -11-16% (18,19), and than the reported early repolarization (ER) prevalence in general population -4.5% (23). However, ER is known to be an age-dependant phenomenon, and in age group 60-70 years, corresponding the average age at the moment of historical ECG in our study, its prevalence appears to be in the range of 1.5% in women and 2-3% in man (23) thus being in line with our observations.…”
Section: Discussioncontrasting
confidence: 51%
“…Recently, a number of studies reported the association between J-wave pattern on historical ECG and life-threating ventricular arrhythmias and sudden death during acute ischemic event (18)(19)(20)(21). The association of a initially existing J-wave pattern with future arrhythmic complications during acute STEMI was explained by the presence of heterogeneity of ventricular repolarization as a substrate predisposing to the development of ventricular arrhythmias in the setting of an acute ischemia trigger (22).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies showed a higher mortality risk in subjects with the ER pattern in specific clinical scenarios (heart failure, ischaemic heart disease) [28,29] in the general population [24] and, which might indeed be concerning, in high endurance athletes [10].…”
Section: Nsmentioning
confidence: 98%
“…Hier sind Daten hinsichtlich der Prävalenz einer ER bei herzgesunden Probanden sowie Prävalenz und Prognose einer ER in einer großen populationsbasierten Studie publiziert worden [1,2]. Ferner rückt mehr und mehr die prognostische Wertigkeit einer ER bei Patienten mit akuten Koronarsyndromen in den Fokus des Interesses [3,4]. Hinsichtlich neuer nichtinvasiver elektrophysiologischer Parameter wurde erstmals ein interessanter Prädik-tor für den plötzlichen Herztod beschrieben, der nach einer Belastungsuntersuchung die Erholung des räumlichen QRS/ T-Winkels beschreibt [5].…”
unclassified
“…In zwei weiteren Studien [3,4] wurde der Hypothese nachgegangen, dass das Vorliegen einer ER mit einer erhöh-ten Vulnerabilität für lebensbedrohliche Tachyarrhythmien während eines akuten koronaren Ereignisses/eines Myokardinfarkts einhergeht. In der Studie von Tikkanen et al [3] …”
unclassified